PENGARUH FINANCIAL DISTRESS, GROWTH OPTIONS, INSTITUTIONAL OWNERSHIP, DAN DEBT TO EQUITY RATIO (DER) TERHADAP AKTIVITAS HEDGING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - D. Purba, Erny Luxy; Rajagukguk, Monica Aprillia (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2020)
ABSTRACT : This research aims to determine the effect of Financial Distress, Growth Options, Institutional Ownership and Debt to Equity Ratio (DER) on Hedging Activities in Manufacturing companies listed on the Indonesia Stock Exchange 2016-2019. To achieve that goal, this research using quantitative research methods to examine the population or a specific sample in order to test the hypothesis that have been set. The technique of data collection is done by libraries and documentation techniques. This research using the method of logistic regression because this method is the most representative to examine the variables examined. The results of this research indicate: (1) Financial distress has an effect on hedging activity (2) Growth Options has no significant effect on hedging activity (3) Instititional ownership has an effect on hedging activity (4) Debt to equity ratio has an effect on hedging activity. And simultaneously financial distress, growth options, institutional ownership and debt to equity ratio affect hedging activity.Keywords : Financial Distress, Growth Options, Institutional Ownership, Debt to Equity Ratio, Hedging.